Improving Dental Service Utilization Rate Using a Proactive Telephone-Based Scheduling Strategy in Primary Healthcare - Juan Carlos Garrido; Daniela Matamala; Ricardo Cartes-Velásquez; Valeria Campos (Association of Support to Oral Health Research (APESB), 2022)
Objective: To determine the effect of a proactive telephone-based scheduling strategy to improve dental service utilization rate in primary healthcare. Material and Methods: A retrospective study was carried out based on the dental appointments' records of a primary healthcare center before-strategy and after-strategy periods. The variables studied for both periods were the number of dental appointments requested, dental appointments undergone, no-shows, and available quotas. Data collection was performed by two researchers between May and June 2018. Descriptive statistics were used to calculate the absolute and relative frequencies. Results: A total of 10,193 records of dental appointments were registered within the two periods. After-strategy period, dental appointments undergone increased by 16,7%, no-shows decreased by 3%, and available quotas decreased by 21.3%. Conclusion: A proactive telephone-based scheduling strategy increased the dental service utilization rate in primary healthcare.